Performance Assessment of a set of Multi-Objective Optimization Algorithms for Solution of Economic Emission Dispatch Problem - Mishra, Sarat; Mishra, Sudhansu Kumar (Informatica, 2020)
This paper addresses the realistic economic emission dispatch (EED) problem by considering the operating fuel cost and environmental emission as two conflicting objectives, and power balance and generator limits as two constraints. A novel dynamic multi-objective optimization algorithm, namely the multi-objective differential evolution with recursive distributed constraint handling (RDC-MODE) has been proposed and successfully employed to address this challenging EED problem. It has been thoroughly investigated in two different test cases at three different load demands. The efficiency of the RDC-MODE is also compared with two other multi-objective evolutionary algorithms (MOEAs), namely, the non-dominated sorting genetic algorithm (NSGA-II) and multi-objective particle swam optimization (MOPSO). Performance evaluation is carried out by comparing the Pareto fronts, computational time and three non-parametric performance metrics. The statistical analysis is also performed, to demonstrate the ascendancy of the proposed RDC-MODE algorithm. Investigation of the performance metrics revealed that the proposed RDC-MODE approach was capable of providing good Pareto solutions while retaining sufficient diversity. It renders a wide opportunity to make a trade-off between operating cost and emission under different challenging constraints.